Trajectoire sociopolitique d’un indicateur de biodiversité forestière : le cas du bois mort - Philippe Deuffic; Christophe Bouget; Frédéric Gosselin (VertigO, 2016)
In order to prove the high level of biodiversity in the French forests, public authorities decided to choose dead wood volume as a referential indicator in 2011. This choice resulted from a long scientific and sociopolitical process that has elevated lack of deadwood – yet traditionally ignored by forest stakeholders – as an environmental public issue. After a moment of confusion, tests, and argumentative construction to catch decision makers’ attention, scientists finally proved the importance of dead wood for biodiversity thanks to an intense work of categorization and objectification. Although the scientific community has succeeded in elevating dead wood as a key indicator of biodiversity, this status is continuously under the threats of scientific advances. Taking into account the diversity of dead wood logs seems indeed more interesting than measuring the volume alone. Likewise, innovative metric processes such as AND barcoding provide more precise information on saproxylic biodiversity than the volume of dead wood that could appear as an outdated metrics. Nevertheless other factors such as data collection costs, practicability of implementation, and communicability towards forest managers, may convince public authorities to keep dead wood volume as a referential indicator. The double status of deadwood which is simultaneously a handy and stable indicator for forest management and also an on-going research object, may evolve significantly according to the scientific and political choices that will be made in the next decade.